مكافحة الهجرة غير الشرعية في حوض البحر الأبيض المتوسط في ظل الإتفاقيات الدولية والتشريعات الوطنية - بوكورو, منال (جامعة الوادي University of Eloued, 2018)
This article deals with the reality of the illegal immigration in the Mediterranean Sea and its origins and the ways to fight it legally as it is one of the primary subjects of the schedule of countries of the region whether they are receiving and transit countries for its unsafe consequences on economic, social and security levels that leads to make many international agreements and national legislations in the frame of the international and national laws to fight this phenomenon its negative impact on peace and security of Mediterranean Rim
Keywords: illegal immigration ; the Mediterranean Sea ; Illegal immigrants ; reasons of illegal immigration ; legal system